2016
DOI: 10.3892/etm.2016.3027
|View full text |Cite
|
Sign up to set email alerts
|

Yi Qi Qing Re Gao-containing serum inhibits lipopolysaccharide-induced rat mesangial cell proliferation by suppressing the Wnt pathway and TGF-β1 expression

Abstract: Abstract. The aim of the present study was to investigate the effect of Yi Qi Qing Re Gao-containing serum (YQ-S) on rat mesangial cell (MC) proliferation and to investigate the underlying mechanism. MCs were divided into the control, lipopolysaccharide (LPS)-stimulated, YQ-S and fosinopril-containing serum (For-S) groups, and cultured for 48 h. An MTT assay was used to evaluate the proliferation of MCs. In addition, reverse transcription-quantitative polymerase chain reaction and western blot analysis were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In the present study, we explored the effect of MB and MP co-administration mediated by US on LPS-induced HMC proliferation, apoptosis, and inflammatory mediator expression (NF-κB and TGF-β1) in vitro. Similar to previous studies (Xue et al, 2011;Li et al, 2015;Yang et al, 2016), LPS markedly induced HMC proliferation, increased NF-κB and TGF-β1mRNA and protein expression, and reduced HMC apoptosis in the present study. The LPS-induced inflammatory response was inhibited in a dose-dependent manner by treatment with different concentrations of MP alone, especially in the 75 μg/mL and 100 μg/mL MP groups compared to the 12 μg/mL and 30 μg/mL MP groups.…”
Section: Lps Is An Endotoxin That Can Exacerbatesupporting
confidence: 80%
“…In the present study, we explored the effect of MB and MP co-administration mediated by US on LPS-induced HMC proliferation, apoptosis, and inflammatory mediator expression (NF-κB and TGF-β1) in vitro. Similar to previous studies (Xue et al, 2011;Li et al, 2015;Yang et al, 2016), LPS markedly induced HMC proliferation, increased NF-κB and TGF-β1mRNA and protein expression, and reduced HMC apoptosis in the present study. The LPS-induced inflammatory response was inhibited in a dose-dependent manner by treatment with different concentrations of MP alone, especially in the 75 μg/mL and 100 μg/mL MP groups compared to the 12 μg/mL and 30 μg/mL MP groups.…”
Section: Lps Is An Endotoxin That Can Exacerbatesupporting
confidence: 80%
“…T-cell cytokines, including IFN-γ, have also been detected in nephritic kidneys ( 30 ). Furthermore, TGF-β1, as an important cytokine, has been demonstrated to promote extracellular matrix synthesis and secretion, and lead to mesangial cell proliferation ( 31 ). Therefore, the measurement of inflammatory cytokine IFN-γ, TNF-α and TGF-β1 levels is of great significance for predicting the development of LN.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the main molecular chaperones of endoplasmic reticulum stress, such as glucose-regulated protein 78 (GRP78) and GRP94, and cytoskeletal regulatory proteins, such as α-actin-4, synaptopodin, desmin, and uPAR, were all inhibited by YQQRG ( Yang et al, 2016a ). An in vitro experiment indicated that treatment with serum-containing YQQRG inhibited LPS-induced rat mesangial cell proliferation, downregulated mRNA and protein levels of Wnt4 and TGF-β1, and reduced the aggregation of the mesangial matrix ( Yang et al, 2016b ). Dioscin might be the key component in YQQRG to exert the above effects.…”
Section: Tcm For Treating Ckdmentioning
confidence: 99%